Ownership structure effect on the extent of segment disclosure: evidence from Malaysia - Johari, Jalila; S., Devi (Elsevier, 2012)
This study examines the relationship between family and founding family ownership, government link companies (GLC) ownership, foreign ownership and widely dispersed ownership and segment disclosure provided by Malaysian listed firms. This study presents a more detailed analysis of segment information disclosure by utilizing both financial and non-financial data to compute the segment disclosure index that is a more robust measure of segment disclosure. We find that the increase in the family and founding family ownership influences the segment disclosure, while the GLC, foreign ownership and widely dispersed ownership have no significant effect on the segment disclosure. We also find that size of the audit firm; listing status and leverage have a significant effect on the segment disclosure.